Homologous Expression and Quantitative Analysis of T3SS-Dependent Secretion of TAP-Tagged XoAvrBs2 in Xanthomonas oryzae pv. oryzae Induced by Rice Leaf Extract - Kim, S.H., Konkuk University, Seoul, Republic of Korea; Lee, S.E., Monsanto Korea, Inc., Vegetable Seeds Division, Cheongwon, Republic of Korea; Hong, M.K., Konkuk University, Seoul, Republic of Korea; Song, N.H., Sangmyung University, Seoul, Republic of Korea; Yoon, B., Kyonggi University, Suwon, Republic of Korea; Viet, P.T., Konkuk University, Seoul, Republic of Korea; Ahn, Y.J., Kyonggi University, Suwon, Republic of Korea; Lee, B.M., National Academy of Agricultural Science, RDA, Suwon, Republic of Korea; Jung, J.W., Konkuk University, Seoul, Republic of Korea; Kim, K.P., Konkuk University, Seoul, Republic of Korea; Han, Y.S., Konkuk University, Seoul, Republic of Korea; Kim, J.G., National Academy of Agricultural Science, RDA, Suwon, Republic of Korea; et al. (Journal of microbiology and biotechnology, 2011)
Xanthomonas oryzae pv. oryzae (Xoo) produces a putative effector, XoAvrBs2. We expressed XoAvrBs2 homologously in Xoo with a TAP-tag at the C-terminus to enable quantitative analysis of protein expression and secretion. Addition of rice leaf extracts from both Xoo-sensitive and Xoo-resistant rice cultivars to the Xoo cells induced expression of the XoAvrBs2 gene at the transcriptional and translational levels, and also stimulated a remarkable amount of XoAvrBs2 secretion into the medium. In a T3SS-defective Xoo mutant strain, secretion of the TAP-tagged XoAvrBs2 was blocked. Thus, we elucidated the transcriptional and translational expressions of the XoAvrBs2 gene in Xoo was induced in vitro by the interaction with rice and the induced secretion of XoAvrBs2 was T3SS-dependent. It is the first report to measure the homologous expression and secretion of XoAvrBs2 in vitro by rice leaf extract. Our system for the quantitative analysis of effector protein expression and secretion could be generally used for the study of host-pathogen interactions.